Atrial Fibrillation as a Rare Complication of the Use of Nifedipine as a Tocolytic Agent: A Case Report and Review of the Literature - Nikolina P. Docheva; Emily D. Slutsky; Roger Sandelin; James W. Van Hook (Case Reports in Obstetrics and Gynecology)
Calcium channel blockers are commonly used tocolytic agents on Labor and Delivery units worldwide as part of the management of preterm labor. Despite their overall reassuring safety profile, rare cardiovascular complications have been reported. In this report, we describe the case of threatened preterm labor managed with nifedipine with subsequent development of atrial fibrillation. This type of cardiac arrhythmia may have considerable consequences for both the mother and the fetus. The aim of this case report and comprehensive review of the literature is to raise awareness.